The Effect of Brand Image, Product Quality and Price on Consumer Attitudes - Wijaya, Indra; Wahyudi, Triyono Arief (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Repurchase interest is the most important target in the field Repurchase interest is the most important target in the marketing sector, so companies must pay attention to related factors. The aim of this research is to determine the moderating role of gender on the influence of brand image, product quality and price on consumer attitudes and their impact on repurchase intention. This type of research is correlational with a quantitative approach. The data collection technique will begin by distributing an initial questionnaire to 30 respondents to determine valid statements, which will then be analyzed using factor analysis. The data collected was processed using (PLS-SEM). Brand Image, Product Quality, Price influence Consumer Attitudes and Consumer Attitudes influence Repurchase Intention. Gender has a moderating effect on the influence of Brand Image and Price on Consumer Attitudes. Gender does not have a moderating effect on the influence of product quality on consumer attitudes and repurchase intention. Companies should improve their brand image by providing customer ideas, creating digital marketing that is considered effective and conducive, using good quality raw materials to produce a good perception of the product and further researchers should expand the scope of research variables.